ANALISIS PENGARUH MOTIVASI SPIRITUAL, KEPEMIMPINAN SPIRITUAL TERHADAP KINERJA RELIGIUS DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) SEBAGAI VARIABEL INTERVENING (Studi Kasus : Guru Taman Kanak-Kanak dan Sekolah Dasar Islam Terpadu di Kota Pontianak dan Kabupaten Kubu Raya) - Apriandika, Muhammad Nahruddin B1021151026 (Jurnal Manajemen Update, 2019)
The TKIT and SDIT environment which is so strong the nuances of Islam are indicative of spiritual motivation, spiritual leadership and religious performance and the school management has not interpreted the importance of OCB. This study aims to examine and analyze the mediating role of Organizational Citizenship Behavior (OCB) on the influence of spiritual motivation, spiritual leadership on religious performance in kindergarten and integrated Islamic elementary school teachers in Pontianak City and Kubu Raya District. This research uses the quantitative method (survey). The population in this study is the number of teaching staff or teachers in Al-Karimah TKIT-SDIT, Al-Mumtaz TKIT-SDIT, and Al-Fityan TKIT-SDIT. The number of samples of 57 respondents was selected by means of Disproportionate Stratified Random Sampling, then data processing using path analysis. The results of the first model showed that spiritual motivation had a positive and significant effect on Organizational Citizenship Behavior (OCB) and spiritual leadership had a positive and significant effect on Organizational Citizenship Behavior (OCB). The ability of these variables in explaining their influence on religious performance was 31.5% while the remaining 68.5% was explained by other factors outside the research model. The results of the study for the second model showed that the variable of spiritual motivation had a positive and significant effect on religious performance, while spiritual leadership had a negative and not significant effect on religious performance and Organizational Citizenship Behavior (OCB) had a positive and significant effect on religious performance. The ability of this variable in explaining its effect on organizational commitment is 20.7% while the remaining 84.9% is explained by other factors outside the research modelKeywords: Spiritual, Motivation, Leadership, Organizational Citizenship Behavior (OCB), and Religious PerformanceDaftar PustakaAbas, J.A. 2009. Level of Existence and Motivation in Islam, Journal of Management History Vol. 15 No. 1, 2009 pp. 50â€“65.Adam, L.O.B., 2012. Peran Motivasi Spiritual Agamis terhadap Organizational Citizenship Behavior (OCB) dan Kinerja Dosen (Studi pada Dosen Universitas Haluoleo Kendari). Jurnal Aplikasi Manajemen, Vol.3 N0. 4Agustin, E., 2015, Pengaruh Motivasi Kerja Terhadap Kinerja Guru Sekolah Dasar Dabin Iv Kecamatan Kajen Kabupaten Pekalongan, Skripsi Dipublikasi, Universitas Negeri SemarangAnshari, 1993. Wawasan Islam. Pokok-Pokok Fikiran Tentang Islam dan Ummatnya. Jakarta. Raja Grafindo PersadaArinnandya, Quisty & Hukama, La Diadhan., 2018. Pengaruh Kepuasan Kerja, Persepsi Dukungan Organisasi Dan Kepemimpinan Spiritual Terhadap Organizational Citizenship Behavior Pada PT MNC Sky Vision Tbk. Jurnal Ilmu Manajemen UPB Vol 6 No.2, 55-63Ancok, Jamaludin (1994), Psikologi Islam, Pustaka Pelajar: Yogyakarta.Bolino, M.C., Turnley, W.H., and Bloodgood, J.M. ( 2002). Citizenship Behavior and the Creation of Social Capital in Organization. Academy of Management Journal,Vol. 7, No. 4, pp. 502 â€“ 522Cahyono, Ari, 2012. Analisa Pengaruh Kepemimpinan, Motivasi dan Budaya Organisasi Terhadap Kinerja Dosen Dan Karyawan Di Universitas Pawyatan Daha Kediri. Jurnal Ilmu Manajemen, Revitalisasi, Vol. 1, No. 1Cushway, Barry. 2007. Human Resource Management. Jakarta: PT Elex Media Komputindo.Djati, S. Pantja. 2009. â€œPengaruh Moral dan Komitmen Staf Administrasi Terhadap Organizational Citizenship Behaviour dan Pengaruhnya Terhadap Kinerja Service Quality di Universitas Swasta Surabaya â€“ Indonesia.â€ Jurnal Aplikasi Manaemen. Vol 7. No 3. Agustus 2009.Frimayanti, A. I., 2015. Latar Belakang Sosial Berdirinya Lembaga Pendidikan Islam Terpadu Di Indonesia. Jurnal Pendidikan Islam, Volume 6Fry, Louis W. (2003). Toward a theory of spiritual leadership. Tarleton State University â€“ Central. Greenwich: Elsevier Inc. 2003.Ghozali, Imam. (2011). Aplikasi Analisis Multivariat dengan Program SPSS. Semarang : Badan Penerbit Universitas DipenogoroGhozali, Imam. (2013). Aplikasi Analisis Multivariate Dengan Program IBS SPSS 21. Semarang : Badan Penerbit Universitas DipenogoroGorda. AA. Suryadinatha NO, 1998, Faktor Internal dan Eksternal Individu Yang Mempengaruhi Komitmen, Disertasi Doktoral dipublikasi, Universitas AirlanggaHasibuan, Malayu S.P.. â€œManajemen Sumber Daya Manusiaâ€. Edisi Revisi, Jakarta: PT. Bumi Aksara. 2012.Janssen, Onne and Yperen, Nico W. Van. (2004). Employeesâ€™ Goal Orientations, the Quality of Leader-Member Exchange, and the Outcomes of Job Performance and Job Satisfaction. Academy of Management Journal 47 (3), 368-384.Kian et al., 2013. Relationship between Motivationss and Citizenship Performance among Generation X and Generation Y. International Journal of Academic Research in Business and Social Sciences, Vol.3 No.11:53-63.Kuncoro Mudrajad, 2003. Metode Riset untuk Bisnis dan Ekonomi, Penerbit Erlangga, Jakarta.Muafi,. 2003 Pengaruh Motivasi Spiritual Karyawan Terhadap Kinerja Religius: Studi Empiris Di Kawasan Industri Rungkut Surabaya (SIER), Yogyakarta. Jurnal JSB Nomor 8 Vol. 3.Muhdar et al., 2013. The Influence of Spiritual Intelligence, Leadership, and Organizational Culture on Organizational Citizenship Behavior and Employees Performance (A Study on Islamic Banks in Makassar, South Sulawesi Province, Indonesia). The International Journal Of Business & Management, Vol 3 Issue 1Mursi, MU, 1997 Sumber Daya Manusia yang Produktif, Jakarta Gema Insani Pers.Neuman, George A. dan Kickul, Jill R. (1998). Organizational Citizenship Behaviors: Achievement Orientation And Personality. Journal Of Business and Psychology 13( 2), pp. 263-279.Organ, D. P., & MacKenzie, S. (2006). Organizational Citizenship Behavior: It's Nature, Antecedents, and Consequences.Rahmawaty, Anita., 2016. Model Kepemimpinan Spiritual Dalam Meningkatkan Kepuasan Kerja Dan Kinerja Karyawan di BMT se-Kabupaten Pati. Iqtishadia Vol. 9, No. 2Rivai, Veithzal. 2010. Kepemimpinan dan Perilaku Organisasi. Jakarta. PT. Raja Grafindo Persada.Roziqin, M., 2010. Kepuasan Kerja. Malang : Averroes Press.Robbins, Stephen P. dan Timothy A. Judge. 2015. Perilaku Organisasi Edisi 16. Diterjemahkan oleh Ratna Saraswati dan Febriella Sirait. Jakarta: Salemba Empat.Robert Bacal. 2005. Performance Management. Dalam Asâ€™Ad. 1995(Ed.), Definisi Motivasi. Jakarta : GMSantoso S, 2003, Buku Latihan SPSS, Strategi Parametrik. PT. ElekSarwono. 2013. Analisis Jalur untuk Riset Bisnis dengan SPSS. Yogyakarta. Andi OffsetShofwa, Yoiz., 2013. Pengaruh Motivasi Spiritual Dan Kepemimpinan Spiritual Terhadap Kinerja Religius Dosen Dan Karyawan Stain Purwokerto. Jurnal Pro Bisnis Vol. 6 No.1Simamora, Hendry. 2007. Manajemen Sumber Daya Manusia. Bagian Penerbitan Sekolah Tinggi Ekonomi YKPN. JogjakartaSoentoro, D. P. 2013. Pengaruh Motivasi Kerja, Kepemimpinan, Lingkungan Kerja Terhadap Organizational Citizenship Behavior Dan Kepuasan Kerja Di PT Sucofindo Surabaya.Sugiyono. 2014. Metode penelitian. Bandung: Alfabeta.Sugiyono. 2016. Metode PenelitianManajemen. Bandung: Alfabeta.Sutarto, Dasar-Dasar Kepemimpinan Administrasi, (Yogyakarta: Gadjah Mada University Press, 2012), hlm. 11.Tasmara, T., 1995, Etos Kerja Pribadi Muslim, Jakarta : Dana Bhakti WakafTicoalu, L. Kartini, 2013, Organizational Citizenship Behavior (OCB) Dan Â Komitmen Organisasi Pengaruhnya Terhadap Kinerja Karyawan. Jurnal EMBA Vol.1 No.4 Desember 2013, Hal. 782-790Titisari, Purnamie. 2014. Peranan Organizational Citizenship Behavior (OCB) Dalam Meningkatkan Kinerja Karyawan. Jakarta: Mitra Wacana Media.Waspodo, A., & Minadaniati, L. 2012. Pengaruh Kepuasan Kerja dan Iklim Organisasi terhadap Organizational Citizenship Behavior (OCB) Karyawan pada PT. Trubus Swadaya. Jurnal Riset Manajemen Sains Indonesia (JRMSI), 3(1), 1-16.Wibisono, C., 2002, Pengaruh Motivasi Spiritual Terhadap Kinerja Karyawan Sub Sektor Industri Manufaktur di Batamindo Batam. Disertasi doktoral dipublikasi, Universitas AirlanggaWibisono, C. 2017 Determination of Leadership and Spiritual Motivation on The Performance of Employees through the Satisfaction of City Government Employees Batam, Indonesia. Advances in Economics, Business and Management Research, vol. 36. 448-458Wibowo. 2012. Perilaku dalam Organisasi. Jakarta: PT. ErlanggaWidyastuti, N & Palupiningdyah, 2015, Pengaruh Kepuasan Dan Motivasi Kerja Terhadap Kinerja Karyawan Dengan Organizational Citizenship Behavior (OCB) Sebagai Variabel Intervening. Management Analysis Journal, Vol. 4 No 1 , 76-78Yusanto, I. 2006. Manajemen Strategis Perspektif Islam, Jakarta, Khairul BayaanZohar, D., dan Marshall, I. 2005. Spiritual Capital: Memberdayakan SQ di Dunia Bisnis. Terjemahan Helmi Mustofa. Jakarta: Mizan Pustaka.Zudjuli SI, 1999. Membentuk Manusia Menjadi Khalifah Di Bumi Yang Mukdaniyah, Surabaya. Pusat Studi Kebijakan AlternatifShofwa, Yoiz., 2013. Pengaruh Motivasi Spiritual Dan Kepemimpinan Spiritual Terhadap Kinerja Religius Dosen Dan Karyawan Stain Purwokerto. Jurnal Pro Bisnis Vol. 6 No.1